2002
DOI: 10.1080/10408390209351916
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition ofHelicobacter pyloriAdhesion to Human Gastric Mucus by a High-Molecular-Weight Constituent of Cranberry Juice

Abstract: A high-molecular-weight constituent of cranberry juice has been found to inhibit the sialyllactose specific adhesion of Helicobacter pylori strains to immobilized human mucus, erythrocytes, and cultured gastric epithelial cells. Different isolates of H. pylori differ in their affinity to the cranberry juice constituent. Cranberry juice may also inhibit adhesion of bacteria to the stomach in vivo, and may prove useful for the prevention of stomach ulcer that is caused by H. pylori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(53 citation statements)
references
References 16 publications
0
50
0
3
Order By: Relevance
“…Nowadays, consumers are increasingly interested in their personal health and expect the foods to be sensory attractive and also safe and healthy. In the last years, in vitro and clinical studies have focused on certain microbial effects by cranberry phenolics [55]; condensed tannins of cranberry can inhibit the adhesion of uropathogenic fimbriated Escherichia coli to uroepithelial cells in the urinary tract [56,57]. Some extracts of cranberry have been also reported to inhibit the adherence of uropathogenic E. coli as well as the inhibition of the sialic-acid-specific adhesin of Helicobacter pylori to human gastric mucosa, a critical step in gastric ulcer development [58].…”
Section: Berry Phenolics and Biological Effects And Human Healthmentioning
confidence: 98%
“…Nowadays, consumers are increasingly interested in their personal health and expect the foods to be sensory attractive and also safe and healthy. In the last years, in vitro and clinical studies have focused on certain microbial effects by cranberry phenolics [55]; condensed tannins of cranberry can inhibit the adhesion of uropathogenic fimbriated Escherichia coli to uroepithelial cells in the urinary tract [56,57]. Some extracts of cranberry have been also reported to inhibit the adherence of uropathogenic E. coli as well as the inhibition of the sialic-acid-specific adhesin of Helicobacter pylori to human gastric mucosa, a critical step in gastric ulcer development [58].…”
Section: Berry Phenolics and Biological Effects And Human Healthmentioning
confidence: 98%
“…It has been recently shown that high molecular weight compounds in cranberry and other berries, probably proanthocyanidins, may also interfere with the adhesion of H. pylori to human gastric mucus and to gastric epithelial cells. 59,60 Furthermore, various extracts of berries, alone or in combination, have been shown to inhibit the growth of H. pylori. 61 Recently Zhang et al…”
Section: Utilization Of Other Functional Dietary Components With Gastmentioning
confidence: 99%
“…The North American cranberry (Vaccinium macrocarpon) and its constituent products have been shown to provide numerous health benefits to humans, including antimicrobial, anti-virus, anti-mutagenesis, antiangiogenesis, and antioxidation (Pappas and Schaich 2009). The anti-microbial activity of cranberry has been widely recognized due to its potency in the prevention of urinary tract infections (Walker et al 1997) and probably stomach ulcers (Burger et al 2002), as well as improvement of oral hygiene (Steinberg et al 2004). The anti-microbial effect is likely attributable to the ability of cranberry to interfere with the adhesion of pathogens to the surfaces of host cells (Howell 2007;Sobota 1984).…”
Section: Introductionmentioning
confidence: 99%